Navigating Divorce in the Global South: Comparative Insights into Legal Procedures and Gender Implications in Muslim-Majority Countries - Wadi, Lalu Tambeh; Muhasim, Ahmad; Sado, Arino Bemi; Muhammad Haydar Al Kautsar (Institut Agama Islam Negeri Kendari, 2025)
Although research on divorce has been extensively documented, studies focusing on the Global South remain limited. To address this research gap, this study aims to analyze a comparative overview of divorce regulations in Indonesia, Malaysia, Pakistan, Egypt, Morocco, Tunisia, and Turkey, highlighting implementation procedures and their impacts. This study employs a content analysis design of the divorce regulations applicable in the seven countries. The method used is normative research with a comparative approach. The study is grounded in Islamic family law theory as the analytical framework. The findings indicate that in Indonesia and Malaysia, divorce is processed through religious courts, with child custody and alimony rights ensured, although property division remains conservative. Pakistan permits unilateral talaq, but legal procedures for women are complex to access, and social stigma is high. Egypt, Morocco, and Tunisia grant broader rights to women, with fair property division and protection of child custody rights. Turkey combines Islamic and secular law with equitable procedures. Similarities lie in child custody and alimony rights, while differences exist in women’s access, property division, and socio-cultural impacts. Challenges include unequal rights, social stigma, and complex legal procedures. Opportunities for legal reform involve expanding women’s rights and fair property distribution. The study’s implications emphasize the need for reforms in Islamic family law to enhance gender equality and protect women’s rights. Keywords: Divorce, Comparative Law, Global South